Dialektika Komunikasi pada Debat Pilpres 2019 dalam Perspektif Al-Qur’an - Wahab Nur Kadri (El Madani : Jurnal Dakwah dan Komunikasi Islam, 2020)
The 2019 Presidential Debate contained in the Qur'an about the Jadal verses through the Dialectic Communication perspective also by studying more deeply and philosophically. This discussion leads the author to discuss the science of communication and the Qur'an with stories and history in a special discussion: about the schedule that arises due to the "message" that comes after there is news of a saliha woman opened by Khaulah bint Tsa'labah; about the Qur'an quoting itself in discussions with the dialectic of the Jadal concept through forms of communication (guidance and revelation) conveyed to the Apostles and humans on earth; The Muslim Ummah needs the Qur'an from an oral tradition that is moving towards the written tradition (the tabi'in, Islamic scholars and thinkers and so on) in analyzing Jadal, where the classical tradition would never be expected. Next schedule; about the form of Jadal in the Al-Qur'an needs to be reviewed transmitted and transformed in the present and future context, such as in the contestation of the Presidential Debate, Pilgub, Pilkada, even in social, cultural, ideological, and religious (Islamic) discourses. Through literature study methods with thematic analysis understanding Jadal in the Qur'an can be analyzed in a complete and objective manner. The implication, as part of the science of communication in the frame of the Qur'an, Jadal understanding has a strong significance because it can enlighten human insight into morality morals.